The effect of reward policy on the motivation and performance of physical education teachers in elementary schools surabaya city - Hernovianus, Intan Pratiwi; Amalia, Kaniati; Khamidi, Amrozi; Purwoko, Budi; Hazin, Mufarrihul (Pendidikan Jasmani, Kesehatan, dan Rekreasi Universitas Nahdlatul Ulama Sunan Giri, 2025)
Physical education, sports, and health teachers have an important role in shaping the character, physical fitness, and discipline of students at the elementary school level. Rewards can be in the form of financial or non-financial rewards given as a form of appreciation for teacher performance. This study uses a quantitative approach with an explanatory research design that aims to test the effect of reward policies on the motivation and performance of physical education teachers in elementary schools in the city of Surabaya. Data collection was carried out by distributing questionnaires directly to teachers at school or through an online platform to facilitate respondents who are in more remote locations. The results of the regression analysis showed that the reward policy had a positive and significant effect on motivation (coefficient = 0.42; p <0.05) and performance (coefficient = 0.38; p <0.05). In addition, motivation also has a positive and significant effect on performance (coefficient = 0.45; p <0.05). The coefficient of determination (r²) value of 0.61 indicates that 61% of performance variability can be explained by the reward and motivation policy variables. Conclusion, reward policy has a positive and significant effect on the motivation and performance of physical education teachers in elementary schools in Surabaya. Further research can expand the object and use different approaches to enrich the findings.